2010
DOI: 10.3810/pgm.2010.09.2201
|View full text |Cite
|
Sign up to set email alerts
|

Does Placebo Response Differ between Objective and Subjective Measures in Children with Attention-Deficit/Hyperactivity Disorder?

Abstract: Placebo response complicates the interpretation of treatment response in both clinical practice and clinical trials in youth with attention-deficit/hyperactivity disorder (ADHD). In a pilot study comparing subjective ADHD symptom rating scales with scores obtained using the Quotient™ ADHD System (an objective computerized technology for assessment of hyperactivity, inattention, and impulsivity in ADHD), it was found that agreement between these 2 measures was not as strong as anticipated. This observation prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…In previous studies comparing subjective ADHD symptom rating scales, with scores obtained using an objective neuropsychological test for the assessment of hyperactivity, inattention, and impulsivity, it was found that agreement between these two measurements was not as strong as anticipated (Manor et al 2008;Sumner et al 2010). These results prompted us to find potential predictors associated with differences between subjective perceptions and objective measurements in children with ADHD treated with MPH.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…In previous studies comparing subjective ADHD symptom rating scales, with scores obtained using an objective neuropsychological test for the assessment of hyperactivity, inattention, and impulsivity, it was found that agreement between these two measurements was not as strong as anticipated (Manor et al 2008;Sumner et al 2010). These results prompted us to find potential predictors associated with differences between subjective perceptions and objective measurements in children with ADHD treated with MPH.…”
Section: Introductionmentioning
confidence: 78%
“…Parent and teacher ratings appear to be influenced by the identity of the person reporting the behavior, rather than by the reported behavior itself. The accuracy of subjective assessments is often questioned because they are prone to the placebo effect (Sumner et al 2010). Another difficulty lies in differentiating between the behavioral response (decreases in the hyperactive-impulsive symptoms) and improvement in attention.…”
Section: Introductionmentioning
confidence: 99%
“…Cb-CPTs consistently demonstrate responsiveness to the effect of stimulants (Rapport et al 1987;Pelham et al 1990;Tabori-Kraft et al 2007;Teicher et al 2008;Fernandez-Jaen et al 2009), and an absence of practice effects is reported (Fernandez-Jaen et al 2009). Recent studies show that cb-CPTs combined with motion tracking systems (MTS) also serve as responsive measures of attention and motor activity in clinical trials (Tabori-Kraft et al 2007;Teicher et al 2008), vulnerability to placebo effects is low (Sumner et al 2010), and a degree of ecological validity has been demonstrated (Teicher et al 2008). …”
Section: Introductionmentioning
confidence: 99%
“…Because ADHD rating forms are vulnerable to placebo (Waschbusch et al 2009) and source (Gomez et al 2003) effects, the inclusion of objective test measures in clinical trials has been recommended by several authors (Teicher et al 2008;Waschbusch et al 2009;Sumner et al 2010). Computer-based continuous performance tests (cb-CPT) are a large family of laboratory tests measuring attention; they are administered in a diversity of forms.…”
Section: Introductionmentioning
confidence: 99%
“…Of particular relevance are continuous performance tests (CPTs), of which many are available (e.g., Corkum and Siegel 1993;Riccio and Reynolds 2001;Homack and Riccio 2006), the Quotient ADHD system (Sumner et al 2010), which pairs a type of CPT with recording of motor activity, and the Neuropsychiatric EEG-Based Assessment Aid (NEBA) quantitative EEG assessment (Snyder et al 2015). CPTs are frequently used in neuropsychological testing, but have less than optimal sensitivity and specificity for diagnosing ADHD.…”
Section: Introductionmentioning
confidence: 99%